(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
It is clear that in recent years, in our country, in accordance with the demands of the 21st century, there have been major changes in many fields, including changes in the field of medicine. In particular, equipment related to the field of endocrinology, laboratory equipment, increase in the level of knowledge as a result of training of medical personnel, patronage service in family polyclinics, rural family polyclinics, privileges created for patients with diabetes in treatment and prevention institutions, and the growth of the people’s consciousness from a cultural aspect. It is observed that the incidence of diseases is increasing.